OS MEMES EM PAUTA: relações com a mídia mainstream no ideal habermasiano de democracia deliberativa - SOUZA, TASSIA AGUIAR DE (2019)
Study on the penetration of memes in the Habermas public sphere and its possible interference in the spaces of political-institutional deliberation. The research aims to identify the presence and approach of political memes of public discussion about the Brazilian political crisis in traditional media vehicles and the incidence of news about political deliberations taken from memetic manifestations in cyberspaceFor this, we take as theoretical reference, Limor Shifman and Viktor Chagas to present the evolution of the studies on the internet memes, as well as their possible classifications; we take Jürgen Habermas to define the public sphere and contextualize an ideal of deliberative democracy in which memes could influence; and Wilson Gomes to problematize the visibility and arguability of the themes in the public agenda The methodology used has a survey of news items that have as a highlight the national political crisis treated by the memes on the Internet and an aesthetic analysis of the memes selected by each vehicle to identify a political position; then a survey of the news brought by the memes as influencers of political-institutional decisions to analyze their interference in the composition of the deliberative democracy idealized by Habermas. The conclusion is that the participation of internet memes in the process of public deliberations in Brazil is a growing phenomenon and that the media, as idealized by Habermas and reiterated by Gomes, actively participates in this system even when it seems to be mere entertainment.